Analisis Persepsi Nilai dan Risiko sebagai Determinan Intensi Penggunaan Layanan Pinjaman Online Berbasis Syariah - Sunaryono, Sunaryono (Jurnal Ekonomi STIEP, 2025)
In the ever-evolving world of digital finance, Islamic online lending services have emerged as a faith-driven alternative to conventional platforms. This study explores how perceived value and perceived risk influence users’ intention to adopt Islamic digital lending services. Drawing from a questionnaire-based dataset, this research employs a quantitative approach to analyze users’ perceptions surrounding service quality, data security, convenience, and ethical concerns. The findings reveal that perceived value such as ease of access, transparency, and alignment with Sharia principles plays a significant role in shaping user intention. Meanwhile, perceived risk including cyber threats, regulatory uncertainty, and misuse of personal data serves as a critical deterrent. The study offers valuable insights for fintech developers, policymakers, and stakeholders seeking to promote sustainable growth in the Islamic digital lending sector. terjemahkan ke indonesia.